Inhibitory Effects of Dietary N-Glycans From Bovine Lactoferrin on Toll-Like Receptor 8; Comparing Efficacy With Chloroquine - Figueroa-Lozano, Susana; Valk-Weeber, Rivca L.; Akkerman, Renate; Abdulahad, Wayel; van Leeuwen, Sander S.; Dijkhuizen, Lubbert; de Vos, Paul (Frontiers in Immunology, 2020)
TLR-8 plays a role in the pathogenesis of autoimmune disorders and associated gastrointestinal symptoms that reduce quality of life of patients. Dietary interventions are becoming more accepted as mean to manage onset, progression, and treatment of a broad spectrum of inflammatory conditions. In this study, we assessed the impact of N-glycans derived from bovine lactoferrin (bLF) on the inhibition of TLR-8 activation. We investigated the effects of N-glycans in their native form, as well as in its partially demannosylated and partially desialylated form, on HEK293 cells expressing TLR-8, and in human monocyte-derived dendritic cells (MoDCs). We found that in HEK293 cells, N-glycans strongly inhibited the ssRNA40 induced TLR-8 activation but to a lesser extent the R848 induced TLR-8 activation. The impact was compared with a pharmaceutical agent, i.e. chloroquine (CQN), that is clinically applied to antagonize endosomal TLR- activation. Inhibitory effects of the N-glycans were not influenced by the partially demannosylated or partially desialylated N-glycans. As the difference in charge of the N-glycans did not influence the inhibition capacity of TLR-8, it is possible that the inhibition mediated by the N-glycans is a result of a direct interaction with the receptor rather than a result of pH changes in the endosome. The inhibition of TLR-8 in MoDCs resulted in a significant decrease of IL-6 when cells were treated with the unmodified (0.5-fold, p < 0.0001), partially demannosylated (0.3-fold, p < 0.0001) and partially desialylated (0.4-fold, p < 0.0001) N-glycans. Furthermore, the partially demannosylated and partially desialylated N-glycans showed stronger inhibition of IL-6 production compared with the native N-glycans. This provides evidence that glycan composition plays a role in the immunomodulatory activity of the isolated N-glycans from bLF on MoDCs. Compared to CQN, the N-glycans are specific inhibitors of TLR-8 activation and of IL-6 production in MoDCs. Our findings demonstrate that isolated N-glycans from bLF have attenuating effects on TLR-8 induced immune activation in HEK293 cells and human MoDCs. The inhibitory capacity of N-glycans isolated from bLF onTLR-8 activation may become a food-based strategy to manage autoimmune or other inflammatory disorders.